On the path independence and invariant of the J-integral for a slant crack and rigid-line inclusion using degenerate kernels and the dual BEM. (1st May 2021) - Chen, Jeng-Tzong; Kao, Jeng-Hong; Kao, Shing-Kai; Huang, Yi-Ling; Chou, Yen-Ting
Abstract: The J -integral and stress intensity factor (SIF) are two major parameters in linear elastic fracture mechanics (LEFM) for the fracture criterion. In this paper, we focus on the J -integral of the slant crack and the slant rigid-line inclusion under the remote anti-plane shear. By employing the degenerate kernel, the path independence of J -integral is analytically demonstrated by using the elliptic coordinates. The positive and negative J -integrals are also analytically derived and numerically implemented by using the dual BEM for the crack and the rigid-line inclusion, respectively. It is interesting to find that the J -integral is not an invariant by using different observer systems but is one component of the vector of the first order tensor. Transformation law of the J -integral with respect to different observers is analytically proved and numerically demonstrated. Finally, the tensor property of order one is examined.